2018
DOI: 10.1002/cam4.1607
|View full text |Cite
|
Sign up to set email alerts
|

CD164 promotes tumor progression and predicts the poor prognosis of bladder cancer

Abstract: CD164 was found to play a role in many malignant diseases. But the roles of CD164 in human bladder cancer have not yet been studied. The object of our study was to investigate the functions of CD164 in urothelial bladder carcinoma. The immunohistochemistry (IHC) was performed to evaluate the associations between the expression level of CD164 and clinical‐pathological features of patients, and IHC was used to analyze the relationship between CD164 and CXCR4 in tumor tissues. Real‐time qPCR and Western blot were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…It is also shown that inhibition of CD164 expression in colon cancer cell line HCT116 reduces cancer cell proliferation, mobility, and metastasis in vitro and in vivo [ 24 ]. CD164 could promote tumor progression and predict the poor prognosis of bladder cancer [ 25 ]. CD164 has also been found to promote lung tumor-initiating cells with stem cell activity and determine tumor growth and drug resistance via Akt/mTOR signaling [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also shown that inhibition of CD164 expression in colon cancer cell line HCT116 reduces cancer cell proliferation, mobility, and metastasis in vitro and in vivo [ 24 ]. CD164 could promote tumor progression and predict the poor prognosis of bladder cancer [ 25 ]. CD164 has also been found to promote lung tumor-initiating cells with stem cell activity and determine tumor growth and drug resistance via Akt/mTOR signaling [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the data from the tumor xenograft model studies revealed that BC growth was inhibited by the overexpression of NFKBIZ, which provided further evidence for the suggested tumor-suppressive role of NFKBIZ in BC. Ki67 has been considered as a useful biomarker for BC, and its expression has been associated with a poor prognosis ( 50 ). In the current study, the upregulated expression levels of NFKBIZ were associated with the downregulated expression levels of Ki67, which is suggestive of an improved prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity and specificity are 81.3% and 63.5% for prediction of lymph node metastasis, 63.1% and 84.2% for the diagnosis of HPV infection. [ 82 ] GHET1 94 patients with cervical cancer vs. 47 normal Tissue Prognostic High GHET1 is associated with poor OS and correlated with clinical stage, distant metastasis, and poor [ 83 ] SNHG14 30 patients (tumor tissue vs. adjacent normal tissue) Tissue Prognostic High SNHG14 has a shorter OS and is positively correlated with tumor size, FIGO stage, and lymph node metastasis [ 84 ] LINC00511 92 cervical cancer tissues vs. 40 adjacent normal tissues Tissue Prognostic High LINC00511 is associated with poor OS and positively correlated with clinical stage, tumor size, lymph node metastasis, histological type of adenocarcinoma, and distant metastasis [ 85 ] PVT1 156 patients with SCCs (tumor tissue vs. adjacent normal tissue) Serum and tissues Prognostic Diagnostic and Prognostic High serum PVT1 has a shorter OS and is positively correlated with tumor size [ 86 ] AFAP1-AS1 TCGA, SRA, GEO and UCSC XENA database Tissue Prognostic High AFAP1-AS1 is positively associated with the TNM stage, high expression and hypomethylation of AFAP1-AS1 is associated with poor OS [ 87 ] lncRNA-ATB 187 patients (tumor tissue vs. adjacent normal tissue) Tissue Prognostic High lncRNA-ATB has a shorter OS and PFS and is positively correlated with SCC antigen level, tumor size, lymph node metastasis, and FIGO stage [ 88 ] GIHCG Plasma (80 patients with cervical cancer vs. 80 normal subjects) Tissue (58 cervical cancer tissue vs. adjacent normal tissue) Serum and tissue Diagnostic The sensitivity and specificity is 88.75% and 87.5% for cervical cancer diagnosis …”
Section: Potential Clinical Application Of Lncrnas In Cervical Cancermentioning
confidence: 99%